2013
DOI: 10.14260/jemds/870
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE STUDY OF MATERNAL & FETAL OUTCOME IN PREGNANCIES OF GESTATIONAL AGE 40 COMPLETED WEEKS AND BEYOND

Abstract: OBJECTIVE:To investigate the etiological factors resulting in Vitamin B12 deficiency in patients with sub-acute combined degeneration (SACD) and other neurological manifestation manifestations. METHODS: We undertook a prospective study of 50 patients, all clinically suspected to have Vit B12 deficiency; they were investigated clinically, hematologically, biochemically and radiologically. RESULTS: There was a dominance of males (41of 50) with the majority in the age group of more than 40 years of age. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
3
11
1
Order By: Relevance
“…10,15 In study by Dobariya PV et al, there were 58 (69.05%) patients in age group 20 to 30 years, and in study by Patel N et al, there were 32 (64%) cases in age group 20 to 30 years. 11,12,16,17 Maximum women (68%) were primigravida in this study similarly Mahapatro et al, found maximum (72%) of patients were primigravida. 13,14 Alfirevic and Walkinshaw, Morgreaset et al, found in their study that primiparity was significantly associated with postterm pregnancy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…10,15 In study by Dobariya PV et al, there were 58 (69.05%) patients in age group 20 to 30 years, and in study by Patel N et al, there were 32 (64%) cases in age group 20 to 30 years. 11,12,16,17 Maximum women (68%) were primigravida in this study similarly Mahapatro et al, found maximum (72%) of patients were primigravida. 13,14 Alfirevic and Walkinshaw, Morgreaset et al, found in their study that primiparity was significantly associated with postterm pregnancy.…”
Section: Discussionsupporting
confidence: 75%
“…Shinge N et al, studied that maximum patients (53.7%) underwent spontaneous vaginal delivery, 9.5% patients required instrumental delivery and 37% patients required caesarean section as mode of delivery. 16,22 The rate of instrumental delivery in this study was 2%, whereas in Mahapatro's study it was found to be 5.72%. 13 In the present study, indication for caesarean section was meconium stained liquor with fetal distress in 8 patients (26%) and failure of induction in 7 cases (21%), which were followed by cephalo-pelvic disproportion in 5 cases (16%), severe oligohydramnios in 6 patient (19%) and non-progress of labour in 5 (15%).…”
Section: Discussioncontrasting
confidence: 66%
“…While in another Indian study maximum patients (53.7%) underwent spontaneous vaginal delivery, 9.5% patients required instrumental delivery and 37% patients underwent caesarean section. 15 Dakshnamurthy et al in their study observed a minimal increase (7%) in the incidence of babies with increased birth weight (>3.6 kg) in the post-dated women at 41 weeks compared to 4% increase among 50 cases of postdated women with labor induction at 40 weeks taken as controls. Kandalgaonkar et al noted that majority (80.2%) of the babies born weighed between 2.5 to 3.5 kg, in present study 61.2% were from birth weight between 2.5 to 3.5 kg.…”
Section: Discussionmentioning
confidence: 90%
“…Present study shows that among maternal complications PPH was 6% and no complications in 87%. A comparative study done by Dr Vijaykumar et al [7] shows rate of PPH was 3.5% and no complications in 87.5%.…”
Section: Discussionmentioning
confidence: 94%
“…Postterm pregnancy associated with an increased risk of postnatal mortality and morbidity including meconium aspiratiom syndrom, oligohydramnios, macrosomia, fetalbirth injuries, septisemia, rate of non reassuring fetal heart rate, fetal distress in labour and maternal complication incresed c.s rate, cephalopelvic disproportion, cervical tear, dystocia, post partamhemorrhage [6]. Management protocol for postterm pregnancy is fetal surveillance for prolonged pregnancy, induction of labour, during intrapartum care proper monitoring of labour [7].…”
Section: Introductionmentioning
confidence: 99%